(untitled) (Historia, 2021)
The second commando against Mzilikaze, undertaken by Andries Hendrik Potgieter, Piet Uys, and Gert Maritz departed from the Suikerbosrand in November 1837. The author provides new information, over and above that of P.J. van der Merwe and R.K. Rasmussen on the history of the Voortrekkers in the Suikerbosrand region. He also makes some disclosures on the battle which previously was not known. Evidence is also provided in respect of the Maritz trek’s place of residence and logistical data.